(untitled) (European Journal of Pure and Applied Mathematics, 2018)
Ditopological texture spaces are simultaneously generalizations of topological, bitopological and fuzzy topological spaces and diframes are generalizations of ditopological texture spaces. In this paper the authors define and study the separation axioms in diframe setting.